Re-greening Tanzania's Usambara - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Axe and fire are destroying the forest of the East Usambara mountains in Tanzania. These forests of northern Tanzania are rich in plants and animals and protect an important watershed. If destruction is not halted, rare and valuable species will...